Hearing Evaluation after Myringoplasty in Underlay Technique (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: to determine the success rate of underlay technique of myringoplasty regarding rate of graft take, complications and hearing improvement.Methods: This Cross sectional study was done in the department of ENT & Head-Neck Surgery, Dhaka Medical College Hospital & Shaheed Suhrawardy Medical college Hospital, Dhaka from July 2012 to December 2012. Sixty(60) patients who underwent myringoplasties were included in the study. All myringoplasty were performed by a postaural approach using autologous temporalis fascia and underlay technique.Results: The total success rate (graft uptake) was 88.3% and of the successful cases an overall hearing improvement was achieved in 73.58% of cases. The mean audiological improvement in air conduction threshold was 13.24 dB & mean closure of the air bone gap was 11.64 dB. The mean values of hearing gain of small perforations and subtotal perforations have shown significant difference.The mean values of hearing gain between posterior perforation and subtotal perforation have shown significant difference.Conclusion: Underlay myringoplasty is an effective technique of repairing the tympanic membrane perforation due to high rate of graft take and marked hearing improvement.Bangladesh J Otorhinolaryngol; October 2016; 22(2): 84-89